Correlates, motivating factors, and barriers of engaging in regular self-reflection among public health students in higher education—A mixed methods approach - Lim, Raymond Boon Tar; Tan, Claire Gek Ling; Hoe, Kenneth Wee Beng; Teng, Cecilia Woon Chien; Müller, Andre Matthias; Azfar, Julian; Narayanasamy, Suganthi; Liow, Chee Hsiang (Frontiers in Public Health, 2022)
Despite the wide implementation of self-reflection in higher education, the body of literature has predominantly focused on students from the clinical health sciences rather than public health. The objective of this study was to evaluate the correlates as well as to explore the motivating factors and barriers of engaging in regular self-reflection among public health students in higher education. We used a mixed methods approach (explanatory sequential design), comprising a cross-sectional survey (quantitative phase) followed by in-depth interviews (qualitative phase). We evaluated the association between reflection frequency as well as the perceptions and facilitators in reflection using the modified Breslow-Cox proportional hazards regression model. Prevalence ratio (PR) was generated. Thematic data analysis was carried out to analyse the qualitative data. Quantitative findings revealed being a regular reflector was positively associated with being more motivated to learn when one applied self-reflection (adjusted PR 1.60, 95% CI 1.17–2.20), the perception of being more prepared for a public health career in the future (adjusted PR 1.28, 95% CI 1.02–1.60), as well as being given enough opportunities to carry out self-reflection in the public health modules (adjusted PR 1.24, 95% CI 1.05–1.45). Qualitative findings revealed most students started their self-reflection mainly due to extrinsic factors such as institutional support, social support, teacher influence and environmental influence. Of these, the most prominent was teacher influence, indicating that they are key agents in promoting self-reflection. Students expressed that it would be important to cultivate intrinsic motivation to sustain their practice of self-reflection along the learning journey such as for the development of career-related professional skills. Other than intrinsic motivation, environmental influences were also important to promote continual reflection among students such as the availability of ample opportunities. Prominent barriers to address included external student factors such as the imbalanced power relationship between teacher and student, and internal student factors such as the perception that self-reflection was too cumbersome and time consuming.